ESSENCE AND MECHANISM OF FORMING HUMAN RESOURCE POTENTIAL OF SECURITY SERVICE OF UKRAINE - Zahutsly A.V. (Pressing Problems of Public Administration, 2015)
The paper, for the first time in the field of public administration, characterizes a system of categories that determine the human resource potential of the Security service of Ukraine, specifies the essence of the phenomenon, formulates the author’s concept, and substantiates the expediency of applying the system and complex approaches to the mechanism of forming human resource potential of the Security service of Ukraine.